On the problems of interaction between government and the private sector to combat corruption (Путеводитель предпринимателя)
The article discusses the problem of corruption, the place of corruption in business, interaction between the governments with the private sector corruption, methods and mechanisms to fight corruption. Cooperation of business-associations with the Agency for State Financial Control and Combating Corruption of the Republic of Tajikistan.